Shallow Bearing Capacity in Cilengkrang, Bandung, West Java, Indonesia - Khoirullah, Nur; Adiwijaya, Annisa Ayungingtyas Pratiwi; Sophian, Irvan; Mulyo, Agung; Muslim, Dicky; Zakaria, Zufialdi (Faculty of Geological Engineering, Universitas Padjadjaran, 2019)
Cilengkrang is located on the eastern side of Bandung City, West Java Indonesia. This area is surrounded by the district of Cimenyan, Cijambe, Cileunyi, and Ujung Berung. The population growth in Cilengkrang area has experienced 1.8% over the last six years as evidenced by the quantity of new housing complexes being built. Due the limitations on available land the development of housing complex is predicted settled in Cilengkrang District. This paper is aimed to determine the characteristic of shallow bearing capacity foundation, as an important factor on constructing a housing complex. To analyze shallow bearing capacity, the soil mechanics data is tested in the laboratory. These samples are taken in 14 sites distribute randomly. Based on the field mapping, the soil that covers the research area is dominated by fine-grained soil as the residual and transported soil product of young and old volcanic products. Based on Universal Classification of Soil (USCS), the high plasticity silt (MH) is dominating this area than the low plasticity silt (ML) and high plasticity clay (CH). Based on shallow bearing capacity foundation data, the allowable bearing capacity in this area ranging from 19.42 to 70 Ton/m2 on square footing. The circular footing values ranging from 19.35 to 69.93 Ton/m2, and continuous footing values ranging from 15.47 to 52.77 Ton/m2.